Intelligent Quad Cane With GPS Allocation For Tachyarrhythmia - Rahim, Norain; Ab Aziz, Ab Wafi; Wan Hassan, Wan Haszerila; Che Aziz, Siti Asma; Abd Rashid, Wan Norhisyam; Rosdi, Rafi’uddin (Penerbit Universiti, UTeM, 2018)
This paper aims to present the development of an Intelligent Quad Cane with Global Positioning System (GPS) Allocation for Tachyarrhythmia. Heart attack symptoms vary between individual. Usually, senior citizen or cardiovascular patient is not aware of their heartbeat rate. Lack of early warning is the most common reason of the patient die because of a heart attack. Thus, this project offers an early warning for the cardiovascular patient to the charged person. Furthermore, this project is able to analyze and indicate an abnormality in heart rate pulse for the user. Sinus tachycardia and Supraventricular tachycardia was chosen as a research subject because this disease is an early complication of the heart attack. The uses of Global System for Mobile (GSM) and GPS modules in this project can make the charged person receives the notification from the patient via Short Message Service (SMS) which contains the exact location together with patient’s condition. This condition shortens the time of ambulance to arrive.